Estimation of new resource allocation in hospital’s (or medical care) inpatient department using discrete event simulation - Rasidi, Nur Fatini; Mohd Yusoff, Nazhatul Sahima; Shuib, Adibah; Md Noh, Abu Yazid; Alias, Suriana; Wan Mohd. Aminuddin, Wan Malissa (Universiti Malaysia Perlis, 2024)
This study presents a computer simulation model for the inpatient department of a public hospital located in Kelantan by using the Discrete Event Simulation approach. Overcrowding, long wait times, and shortages of nurses and beds have been identified as significant issues in the department, which requires a reliable tool for analyzing current operations and optimizing resource allocation to improve service quality. By applying Discrete Event Simulation, the study models the system of the inpatient department and identifies bottlenecks in the process. Arena software was utilized to determine the optimal number of resources needed to meet the demands. The improvement model was developed based on the optimization results, and its conclusive findings demonstrate that the enhanced model significantly improves the performance of the inpatient department in terms of patient waiting time and the utilization rate of nurses and beds. In addition, a new mathematical equation has been developed to generate alternative resource allocation options based on the hospital budget. The implementation of the new configuration of inpatient department resources, as constructed in this study, effectively improves system bottlenecks. The findings of this study can be used to inform decision-making and enhance the efficiency and effectiveness of the inpatient department.